Auction Winner as A New Criteria in The Concept of Good Faith Buyer in Indonesia - Faizal Kurniawan; Xavier Nugraha; Ardhana Christian Noventri; Qona’aha Noor Maajid (Jambe Law Journal, 2021)
Good faith is a principle embodied under Article 1338 Paragraph (3) of the Indonesian Civil Code, which is required in every stage of a contract, including in a land sale and purchase contract. Under several decisions of the Supreme Court, good faith is considered to exist, for instance, when a buyer purchased a land through the auction of the State Receivables Affairs Committee (PUPN). Nevertheless, based on a conviction in the judicial practices, this article believes that purchases through official auctions are not necessarily the indicators for the existence of good faith principle in a land sale and purchase contract. Therefore, this study is focused on the concept of good faith buyer with a land object as well as the characteristic of auction winner as a good faith buyer protected by law. In conclusion, parties of a land sale and purchase contract through auction can be considered to have performed in good faith when they have fulfilled the criteria under Supreme Court Circular Letter and other criteria such as purchasing through state auction office in accordance with the applicable laws and regulations, purchasing in a reasonable price, and the auction winner is not the creditor himself who purchases at a price far below the collateral limit price.